Multifunctional graphene-based magnetic nanocarriers for combined hyperthermia and dual stimuli-responsive drug delivery - Rodrigues, Raquel O. (2018)
The synthesis of hydrophilic graphene-based yolk-shell magnetic nanoparticles functionalized with copolymer pluronic F-127 (GYSMNP@PF127) is herein reported to achieve an efficient multifunctional biomedical system for mild hyperthermia and stimuli-responsive drug delivery. In vitro tests revealed the extraordinary ability of GYSMNP@PF127 to act as smart stimuli-responsive multifunctional nanomedicine platform for cancer therapy, exhibiting (i) an outstanding loading capacity of 91% (w/w, representing 910 μg mg-1) of the chemotherapeutic drug doxorubicin, (ii) a high heating efficiency under an alternating (AC) magnetic field (intrinsic power loss ranging from 2.1-2.7 nHm2 kg-1), and (iii) a dual pH and thermal stimuli-responsive drug controlled release (46% at acidic tumour pH vs 7% at physiological pH) under AC magnetic field, in just 30 min. Additionally, GYSMNP@PF127 presents optimal hydrodynamic diameter (DH = 180 nm) with negative surface charge, high haemocompatibility for blood stream applications and tumour cellular uptake of drug nanocarriers. Due to its physicochemical, magnetic and biocompatibility properties, the developed graphene-based magnetic nanocarrier shows high promise as dual exogenous (AC field)/endogenous (pH) stimuli-responsive actuators for targeted thermo-chemotherapy, combining magnetic hyperthermia and controlled drug release triggered by the abnormal tumour environment. The presented strategy and findings can represent a new way to design and develop highly stable added-value graphene-based nanostructures for the combined treatment of cancer.